Infant-Guided, Co-Regulated Feeding in the Neonatal Intensive Care Unit. Part I: Theoretical Underpinnings for Neuroprotection and Safety - Shaker, Catherine S. (Seminars in Speech and Language, 2017)
The rapid progress in medical and technical innovations in the neonatal intensive care unit (NICU) has been accompanied by concern for outcomes of NICU graduates. Although advances in neonatal care have led to significant changes in survival rates of very small and extremely preterm neonates, early feeding difficulties with the transition from tube feeding to oral feeding are prominent and often persist beyond discharge to home. Progress in learning to feed in the NICU and continued growth in feeding skills after the NICU may be closely tied to fostering neuroprotection and safety. The experience of learning to feed in the NICU may predispose preterm neonates to feeding problems that persist. Neonatal feeding as an area of specialized clinical practice has grown considerably in the last decade. This article is the first in a two-part series devoted to neonatal feeding. Part 1 explores factors in NICU feeding experiences that may serve to constrain or promote feeding skill development, not only in the NICU but long after discharge to home. Part II describes approaches to intervention that support neuroprotection and safety.
Keywords: Premature neonates; feeding; neuroprotection; infant-guided; cue-based